Giant occipital encephalocele: a case report, surgical and anesthetic challenge and review of literature - Soha Zahid (SpringerOpen, 2021)
Abstract Background An encephalocele is a congenital neural tube defect characterized by herniation of cranial contents through a defect in the cranium and is caused by failure of the closure of the cranial part of the developing neural tube. An encephalocele is termed as “giant encephalocele” when the size of encephalocele is larger than the size of the head. They depend on size of the sac, percentage of neural tissue content, hydrocephalus, infection, and other associated pathologies for a favorable neurological outcome. Case presentation We report a case of a four-month-old boy with a giant occipital encephalocele measuring 21 × 15 × 19 cm in size, which was a surgical and anesthetic challenge for us. Intubation was achieved in lateral position. Part of occipital and cerebellar parenchyma was present in the sac and bony defect was approximately 2.5 cm in occipital bone in midline. We performed surgical excision and repair with a good overall outcome. Conclusion Perioperative management of a giant occipital encephalocele is a challenge for both anesthesiologists and neurosurgeons. Managing such a case demands a search for other congenital abnormalities, expertise in handling airway, and proper intraoperative care. Careful planning and perioperative management are essential for a successful outcome.